(untitled) - Shapiro,Jeffrey R. (New York, 2007)
SQL Server 2005 is Microsoft's next-generation data management and analysis software designed to deliver increased scalability, availability, and security to enterprise data and analytical applications while making them easier to create, deploy, and manage.
Keywords: Client/server computing,Mạng máy tính